2015
DOI: 10.1007/s00396-015-3651-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous evolution of self-assembled phases from anisotropic colloidal dispersions

Abstract: We investigate the spontaneous evolution of various self-assembled phase states from a homogeneous aqueous dispersion of high-aspect ratio Montmorillonite (Na Cloisite) nanoclay platelets grounded on the observations made over a period of 3.5 years. We have established the t w -c phase diagram for this system for the first time in salt-free suspensions under normal pH conditions using rheology experiments and have detected that these suspensions do undergo nontrivial phase evolution and aging dynamics. Distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…X-rays scattering experiments [58] have confirmed that for c < 1% wt the scattering intensity progressively increases with waiting time, a signature of a very slow ongoing phase-separation, while for c > 1% wt it approaches a time-independent value, an expected signature of an equilibrium gel. Similar conclusions have resulted from the experimental investigation of other clays, including high aspect ratio Montmorillonite [59]. In all cases, a region of thermodynamic instability has been detected at low densities, consistent with the theoretical expectation by invoking an effective (although unknown) limited valence of the clay particles.…”
Section: Laponitesupporting
confidence: 86%
“…X-rays scattering experiments [58] have confirmed that for c < 1% wt the scattering intensity progressively increases with waiting time, a signature of a very slow ongoing phase-separation, while for c > 1% wt it approaches a time-independent value, an expected signature of an equilibrium gel. Similar conclusions have resulted from the experimental investigation of other clays, including high aspect ratio Montmorillonite [59]. In all cases, a region of thermodynamic instability has been detected at low densities, consistent with the theoretical expectation by invoking an effective (although unknown) limited valence of the clay particles.…”
Section: Laponitesupporting
confidence: 86%
“…For higher concentrations, the samples remained arrested showing no aging. Similar results were also found with other compounds ( 30 33 ), some of which were of biological interest ( 34 , 35 ). More recently, the flexibility offered by DNA nanotechnology ( 36 ), exported to soft matter ( 37 ), has been mastered to generate an experimental system with tunable valence and interaction strength ( 38 ).…”
Section: Introductionsupporting
confidence: 87%
“…It has the capability for soaking up a large amount of water with dramatic osmotic swelling. Hence, it is spontaneously exfoliated into aluminosilicate monolayers and forms stable colloidal dispersion without any physico-chemical treatment or exfoliating agent [8]. Moreover, it is interesting that for the dispersion with high clay concentration, the sol/gel transition occurs and LCs can be observed in the gel.…”
Section: Introductionmentioning
confidence: 99%